The Temporal Expression of Global Regulator Protein CsrA Is Dually Regulated by ClpP During the Biphasic Life Cycle of Legionella pneumophila - Ge, Zhen-huang; Long, Qin-sha; Yuan, Pei-bo; Pan, Xin; Shen, Dong; Lu, Yong-jun (Frontiers in Microbiology, 2019)
Legionella pneumophila, an environmental bacterium that parasitizes protozoa, is the causative pathogen of Legionnaires' disease. L. pneumophila adopts a distinct biphasic life cycle that allows it to adapt to environmental conditions for survival, replication, and transmission. This cycle consists of a non-virulent replicative phase (RP) and a virulent transmissive phase (TP). Timely and fine-tuned expression of growth and virulence factors in a life cycle-dependent manner is crucial. Herein, we report evidence that CsrA, a key regulator of the switch between the RP and the TP, is dually regulated in a ClpP-dependent manner during the biphasic life cycle of L. pneumophila. First, we show that the protein level of CsrA is temporal during the life cycle and is degraded by ClpP during the TP. The ectopic expression of CsrA in a ΔclpP mutant, but not in the wild type, inhibits both the initiation of the RP in vitro and the invasiveness to Acanthamoeba castellanii, indicating that the ClpP-mediated proteolytic pathway regulates the CsrA protein level. We further show that the temporally expressed IHFB is the transcriptional inhibitor of csrA and is degraded via ClpP-dependent manner during the RP. During the RP, the level of CsrA is increased by promoting the degradation of IHFB and reducing the degradation of the accumulated CsrA via ClpP-dependent manner. During the TP, the level of CsrA is decreased by inhibiting the degradation of IHFB and promoting the degradation of the accumulated CsrA via ClpP-dependent manner as well. In conclusion, our results show that the growth-stage-specific expression level of CsrA is dually regulated by ClpP-dependent proteolysis at both the transcription and protein levels during the biphasic life cycle of L. pneumophila.